INCREASE IN ORDER VOLUME AND TOTAL REVENUE OF PHARMACEUTICAL WHOLESALERS THROUGH THE IMPLEMENTATION OF E-COMMERCE - I Putu Sudiatmika Widnyana; Titien Siwi Hartayu (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
Pharmaceutical Pharmaceutical Wholesalers play an essential role in ensuring the availability of medicines within the healthcare service system; however, their distribution performance is often constrained by conventional sales mechanisms. The implementation of e-commerce is expected to improve managerial efficiency and support sales performance in pharmaceutical distribution. This study aimed to assess the impact of e-commerce implementation on increasing order volume and total revenue at the pharmaceutical wholesaler PT. Wahana Fajar Utama in Bali. A quasi-experimental study with a one-group pretest–posttest design was conducted by analyzing transaction data for three months before and three months after the implementation of e-commerce. Data were analyzed using the Shapiro–Wilk normality test (p > 0,05) and the Paired Sample T-Test. The results showed an increase in the average monthly order volume from 194 to 256 (32%) and an increase in the average monthly revenue from IDR 264,723,293 to IDR 396,445,539 (49.7%). Statistical analysis indicated significant differences in both order volume (p value=0.034) and revenue (p value=0.018) before and after the intervention. The implementation of e-commerce was proven to significantly increase order volume and total sales revenue at PT. Wahana Fajar Utama.